Answer:
Check explanation
Step-by-step explanation:
I'll give you my way of solving it and you can figure it out from there.
<CEA = <DEB due to vertical angles
AE = ED due to midpoint theorem
<CAD = <ADB due to alternating angles theorem
thus two triangles congruent due to ASA
Answer:
3xy² - 14y²
Step-by-step explanation:
I hope that this is the problem
- x²y + [ - (x²y - 2xy² + y²) + (xy² - 3y² + x²y)] - (10y² - x²y)
= - x²y + [ - x²y + 2xy² - y² + xy² - 3y² + x²y] - 10y² + x²y
Now combine like terms in the [ ].
= - x²y + [ -x²y + x²y + 2xy² + xy² - y² - 3y² ] - 10y² + x²y
= - x²y + [ 0 + 3xy² - 4y²] - 10y² + x²y
= - x²y + 3xy² - 4y² -10y² + x²y Now combine like terms
= (-x²y + x²y) + 3xy² + (-4y² - 10y²)
= 0 + 3xy² - 14y²
= 3xy² - 14y² or y²(3x - 14)
89 would be the correct answer